The Governance of Artificial Intelligence from the Perspective of Political Phenomenology - Mohammad Karampouri; Rohollah Eslami (Journal of Philosophical Investigations)
In this article, an attempt has been made to explain the governance of AI based on the perspective of political phenomenologists with Morrow's interpretive approach and theoretical framework. The main question is: How does political phenomenology provide insights into the concept of AI governance? According to the hypothesis, the phenomenology of AI governance has a mathematical and positivist rationality. The results of the research also show that political phenomenologists refer to mathematical systems in the process of forming the rule of artificial intelligence; the formal systems of mathematics that create the mathematical world cause the mathematization of the life-world and its political horizon; and finally, the sovereignty of AI emerges. This process is not related to the philosophical development of existence and human freedom, and it is a kind of forgetting the life-world and is in conflict with the human meaning of phenomenology. They consider this process to be the cause of the attenuation of ancient virtues and the distortion of political action in the sense of the political space of the city-state, and while adopting a cosmic vision, anti-modernism mainly shows its dependence on the virtues and rights and natural law of pre-modern political systems against the modern systems of the mathematical world.